The role of subgaleal suction drain placement in chronic subdural hematoma evacuation - Yadav, Yad; Parihar, Vijay; Chourasia, Ishwar; Bajaj, Jitin; Namdev, Hemant (Asian Journal of Neurosurgery, 2016)
Introduction: There is lack of uniformity about the preferred surgical treatment, role of drain, and type of drain among various surgeons in chronic subdural hematoma (CSDH). The present study is aimed to evaluate role of subgaleal drain. Materials and Methods: This was a prospective study of 260 patients of CSDH treated surgically. Burr-hole irrigation with and without suction drain was done in 140 and 120 patients, respectively. Out of 120 patients without suction drain 60 each were managed by single and two burr holes. Pre- and postoperative GCS was recorded. Recurrent hematomas, CSDH secondary to tumor, due to intracranial hypotension, coagulopathy, children below 18 years, and patients treated by twist drill craniostomy or craniotomy were excluded. Subgaleal closed-system drainage with low negative pressure was used. Results: Age of the patients ranged from 18 to 75 years with mean age of 57 years. There were 9, 47, 204 patients in GCS of 3-8, 9-12, and 13-15, respectively. Both the groups were comparable in terms of age, etiology, gender, and neurological status. There was no difference in the mortality in both the group. The recurrence and postoperative pneumocephalus was significantly less in suction drain group as compared to without drain group. There was no infection or any other complication related to suction drainage. Conclusion: Subgaleal closed suction drainage was safe, simple, and effective in the management of CSDH. Recurrence rate was low in the suction drain group.
Keywords: Chronic subdural hematoma; intracranial subdural hematoma; operative surgical procedure; subdural hematoma; subgaleal drainage